The psychological effects of the Corona pandemic (Covid-19) on the Arab citizen and his responses to it: A cross-sectional study in several Arab countries - Abdelfattah, Faisal; Abu-Hilal, Maher; Dodeen, Hamzeh; Alaedein, Jehad; Bahrani, Muna Al; Atoum, Adnan (Dirasat: Human and Social Sciences, 2021)
The Covid-19 outbreak has had severe effects on the humanity and has disrupted aspects of life. Hence, the psycho-social consequences attracted attention after imposing isolation and "social distancing". The current study was conducted to reveal the effects of this pandemic on individuals. Responses were collected electronically through a self-report questionnaire during April 25 to May 17, 2020. Respondents were 1692 citizens from several Arab countries and Arab residents abroad females formed 63.3% and ages ranged between 23 and 50 years at 64.8% of the participants. Results in emotional domain showed, the participants valued the work of medical staff and the efforts made by security services. In cognitive domain, 85% of respondents knew that the possible causes of Coronavirus included: lack of social distancing and chronic diseases. In the domain of behavioral practices, individuals became more aware of hygienic practices, especially hand washing and using sterilizers. People become anxious fearing the possibility that a family member may get infected. Followed by the fear that the pandemic may continue. Females showed higher levels than males on all measures, and older age was associated with an increase in emotional manifestations, behavioral practices, and low feelings of anxiety. Residents of city exceed significantly those living in village only in the behavioral domain, while their response converged in emotions, knowledge, and anxiety. This study has highlighted that the high level of anxiety may be the basis for understanding the issues related to their health, well-being, and the subsequent changes in emotions, knowledge, and behavior.